KUR'AN'A GÖRE PEYGAMBERLERE İTARAZ SEBEPLERİ - ŞEN, SEDA (Fırat Üniveristesi, 2011)
Allah insanı yarattığı andan itibaren onlara doğru gösterecek, ibadetlerini öğretecek peygamberler yollamıştır. Allah bu peygamberleri pek çok ortak sıfat ile de vasıflandırmıştır. Peygamberlerin görevleri sadece Allah'tan aldıkları vahiyleri insanlara bildirmek ve onlara güzel örnek olmaktır. Bu uğurda peygamberler pek çok sıkıntıya katlanmışlardır.Allah'ın gönderdiği bu peygamberlere inananlar olduğu gibi inanmayanlar da olmuştur. İnanmayan bu insanlar peygamberlere itiraz etmişlerdir. İtiraz sebepleri her çağda aynı olmakla beraber kavimlerin kendi özel durumlarına göre farklılık göstermiştir. Mesela her kavim peygamberlerini akılsızlıkla delilikle suçlamışlardır. Yine kendilerine gelen peygamberleri beğenmemiş peygamber olarak insan değil de insanüstü bir varlık beklemişlerdir. Bunun yanında Nuh peygamberin kavmi putlara tapmaktan kurtulamamış, Ad kavmi itibarlarına ve güçlerine çok güvenmiş, Semud kavmi hadlerini aşmış, Lut kavmi sapıklıkta çok ileri gitmiş, Medyen ve Eyke halkları ölçü ve tartıda haksızlık yapmışlar, Musa peygamberin kavmi de nankörlükleriyle hadlerini aşmışlar ve ilahi cezaya çarptırılmışlardır.Anahtar Kelimeler: Allah, Peygamber, Ku'ran, Kavim, İtiraz, Sebepler

From the moment God created man to show them the right, sent the prophets to teach worship. Also equipped with the prophets of God a lot in common adjective. Tasks of the prophets received revelations from Allah only to inform people and be good examples to them. Many prophets relied on this cause trouble.Those who believe in the prophets sent by Allah as believers have been also. Does not believe these people have objected to the prophets. Although the reasons for the appeal of each nation of the same age varied according to their particular circumstances. For instance, every nation who accused the prophets of madness. Yet the prophets not like them as a human prophet and not a human being waited above. In addition, people of Noah worshiped idols, dignity and power of people of very trusted name, puts people of Semud exceeded, Lot tribe went too far in their jobs, Madyan and unfair to scale I made Companions of the Wood and the peoples of the measure, the folk of Moses the prophet and the divine punishment had suffered ingratitude.Key words: Allah, the Prophet, Ku?ran, Kavi, the appeal, the reasons why.
According to the Qur?an prophets the causes of appeals
Keywords: Din